Inflammatory cytokines are associated with response and prognosis in patients with esophageal cancer - Blank, Susanne; Nienhüser, Henrik; Dreikhausen, Lena; Peters, Leila; Heger, Ulrike; Ott, Katja; Schmidt, Thomas (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.17671 Susanne Blank, Henrik Nienhüser, Lena Dreikhausen, Leila Sisic, Ulrike Heger, Katja Ott, Thomas Schmidt